Philip Morris International: equity valuation - Santos, Luís Manuel Pecas dos (2019)
The focus of this dissertation is on the equity valuation of Philip Morris International (PMI), Inc., the main publicly traded tobacco company. For that matter, the main goal of this paper is to determine how much PMI is worth and reach a fair price per share, which means to calculate how much the company worth given its assets and its position in the market. As the objective of the thesis is to value only the equity part, the valuation approach followed the free cash-flow to the equity method. Additionally, is also done an overview of the principal equity valuation approaches, along with other topics considered as essential in a valuation methodology process. Philip Morris International target share price is forecasted at 92$ and when compared with the price as of 31-Dec-18 of 66,76$, the last one is clearly undervalued.